2020
DOI: 10.1097/aln.0000000000003539
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Open-lung Approach, Regional Ventilation, and Lung Injury in Cardiac Surgery

Abstract: Background In the Protective Ventilation in Cardiac Surgery (PROVECS) randomized, controlled trial, an open-lung ventilation strategy did not improve postoperative respiratory outcomes after on-pump cardiac surgery. In this prespecified subanalysis, the authors aimed to assess the regional distribution of ventilation and plasma biomarkers of lung epithelial and endothelial injury produced by that strategy. Methods Perioperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“… 28 Moreover, in a prespecified subanalysis, the authors showed that although open lung ventilation improved dorsal ventilation in the short term, this benefit was not sustained and was associated with greater plasma biomarkers of epithelial lung injury, suggesting lung overdistention. 29 It is plausible that an open-lung strategy may cause lung distention under the intraoperative “open-chest” conditions and that alveolar recruitment already was maximized in the control group.…”
Section: Current Knowledge and Gaps Regarding Ards In Cardiac Surgerymentioning
confidence: 99%
“… 28 Moreover, in a prespecified subanalysis, the authors showed that although open lung ventilation improved dorsal ventilation in the short term, this benefit was not sustained and was associated with greater plasma biomarkers of epithelial lung injury, suggesting lung overdistention. 29 It is plausible that an open-lung strategy may cause lung distention under the intraoperative “open-chest” conditions and that alveolar recruitment already was maximized in the control group.…”
Section: Current Knowledge and Gaps Regarding Ards In Cardiac Surgerymentioning
confidence: 99%
“…Notably, studies focused on RMs during GA do not take into account the recruitability of the lung, which may significantly differ in accordance with patient’s baseline comorbidities and surgical position [ 54 ]. In addition, RMs are usually well tolerated hemodynamically but seem to be not free from the risk of overdistention, as described also in critically ill patients [ 37 ]; a recent RCT, indeed, found higher levels of receptor for advanced glycation end-products, a marker of lung epithelial injury [ 55 ], in patients receiving intraoperative RMs [ 56 ]. Further studies are needed to elucidate which patients should receive intraoperative RM and how.…”
Section: Recruitment Maneuversmentioning
confidence: 99%
“…Even so, sub-group analysis performed in patients with high baseline ∆P suggest some physiological benefit in RM group. Given that intraoperative RM are not free from risk of alveolar injury [ 56 ], one could argue that RM should be limited to patients with higher ∆P. Even so, recommendations based on strong clinical outcomes are still lacking.…”
Section: Special Settings: Thoracic Surgerymentioning
confidence: 99%
“…In this issue of Anesthesiology, Lagier et al 7 report on the effects of the open-lung ventilation strategy on the distribution of ventilation and lung injury in a subpopulation of the PROVECS study. In total, 86 patients were investigated, whereby 56 patients were included in the analysis of distribution of ventilation by electrical impedance tomography, and 30 patients were investigated for biomarkers of lung injury.…”
mentioning
confidence: 99%
“…Lagier et al 7 provide a number of possible explanations for the lack of consistent beneficial effects, and even potentially harmful effects, of the open-lung strategy in this surgical population: (1) most patients included in this subanalysis had no specific respiratory risk; (2) a semirecumbent position was used, which might have reduced lung collapse; (3) de-airing maneuvers before cardiopulmonary bypass, which were part of the surgical protocol, may have recruited lungs of controls, and cardiopulmonary bypass possibly increased the risk of lung collapse; (4) increased respiratory system compliance after sternotomy may have increased transpulmonary pressures; and (5) lack of individualization of PEEP and level of airway pressure during recruitment maneuvers could jeopardize the benefits of the open-lung ventilation strategy. Although they sound plausible, they can also be challenged.…”
mentioning
confidence: 99%